Corrigendum: Methylome changes in Lolium perenne associated with long-term colonisation by the endophytic fungus Epichloë sp. LpTG-3 strain AR37. - Forte FP; Malinowska M; Nagy I; Schmid J; Dijkwel P; Hume DE; Johnson RD; Simpson WR; Asp T (Frontiers Media S.A., 2023)
[This corrects the article DOI: 10.3389/fpls.2023.1258100.]. This article is a correction to: Methylome changes in Lolium perenne associated with long-term colonisation by the endophytic fungus Epichloë sp. LpTG-3 strain AR37
Keywords: DNA methylation; Epichloë sp.; Lolium perenne; artificial association; drought stress; endophytic fungi; generation effect; plant-microbe interactions